THE CORRELATION BETWEEN GRAMMAR MASTERY AND READING SKILL OF THE ELEVENTH GRADERS STUDENTS OF SMK KESEHATAN BHAKTI INDONESIA MEDIKA - Avin Nuril Hikmah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This research aims to find out the correlation between grammar mastery and reading skill. The research problem in this research was stated asâ€œIs there any correlation between grammar mastery and reading skill?â€ then this research has found that there is a significant correlation between the two variables. The population of this reasearch was the the eleventh graders students of SMK Kesehatan Bhakti Indonesia Medika.The researcher used sample which consist of 30 students, with the analysis of Pearson product moment. The instrument of this research was adapted from book Deborah Phillips (2001) entitled Longman Preparation Course for the TOEFL Test: Preparation for the Computer and Paper Tests. The result of this research presented that there is a significant correlation between both of variables. Technique of analysis data in this research calculating coefficient using Pearson Product Moment in SPPS v22. The scores are known from 30 sample (N=30). The result showed the mean of grammar mastery is 83.03 and the mean of reading skill is 91.40. Based on the calculating correlation coefficient, this research has strong correlation because the correlation coefficient is .738. Analysis of data through calculating using Pearson Product Moment by SPSS v22, the data indicated that the sig (2-tailed) value .000 is lower than .05. Based on the result above, the researcher settled that there is a significant correlation between grammar mastery and reading skill of the eleventh graders students of SMK Kesehatan Bhakti Indonesia Medika. The conclusion of this research showed that grammar mastery and reading skill have a significant correlation. It means that if the students have high scores in grammar, they also have high scores in reading skill. On the contrary, if the students have low scores in grammar, they also have low scores in reading skill. So it is important for students to have grammar mastery to get good reading scores as well. The researcher provides some suggestions for the students to increase their practice and to learn grammar which is widely used in reading questions and for the future researchers to conduct similar research by adding a new variable that is vocabulary mastery and give the tests directly to the students.Keywords:Â Correlation, Grammar Mastery, Reading Skill